Evaluation of the effects of a flipped classroom model versus lecture method on BSc nursing students’ knowledge in a health assessment course - Elizabeth K. Kamolo; Sherry Oluchina; Naomi Mutea (International Journal Of Community Medicine And Public Health, 2026)
Background: Conventional teacher-centred pedagogy has dominated nursing education. However, these methods have been associated with passive learning, inability to develop problem-solving and critical thinking skills among nursing students, and an increasing theory and practice gap. Adoption of innovative student-centred teaching methods such as the flipped classroom has been proposed as a strategy to bridge this gap. The study aimed to evaluate the effect of a flipped classroom model versus the lecture method on knowledge acquisition among second-year BSc. nursing students undertaking a health assessment course at a Kenyan University. Methods: A mixed-method study consisting of a non-equivalent control group pre-test post-test quasi-experimental design was adopted. Forty-one students received training through the lecture method, while 39 were exposed to the flipped classroom approach over consecutive academic years. A knowledge test was administered pre-course and post-course. Data were analyzed using descriptive and inferential statistics, including the chi-square test and paired and independent t-tests. Results: There was a significant difference in post-test health assessment knowledge mean scores, with the flipped classroom group attaining higher scores compared to their traditional lecture counterparts (p=0.004). Conclusions: The flipped classroom had a positive effect on nursing students’ knowledge of health assessment. This student-centred pedagogy can be recommended for teaching foundational nursing courses.